Cross-sectional study reveals a high prevalence of vitamin D deficiency among healthy school children in central Kerala, India - Anitha, Ayyappan; Poovathinal, Suresh A.; Viswambharan, Vijitha; Thanseem, Ismail; Vasu, Mahesh M.; M., Ranjitha (International Journal of Contemporary Pediatrics, 2019)
Background: Authors examined serum vitamin D status among the healthy school children belonging to the south Indian state of Kerala. Methods: A cross-sectional study, participants were recruited through medical camps organized in Thrissur and Palakkad districts of central Kerala during the months of March and April 2017. A 174 healthy school children (98 males and 76 females) aged 5-13 years were recruited for the study. The children were found to be healthy on the basis of physical examination by a Paediatrician. None of the children had any symptoms of skeletal deformities. All the children were drug-naive. Data on height, weight, skin color, food habits, physical activities and socio-economic status were recorded. A 2ml of peripheral blood samples were collected from the participants. Total vitamin D in the serum was estimated by chemiluminescence immunoassay (CLIA). Results: VDD was observed in 60.92% and insufficiency in 30.46% of the participants. Only 8.62% of the participants had normal vitamin D levels. The mean vitamin D level was 19.93 ng/ml. Males had significantly higher vitamin D levels compared to females. Factors such as age, height, weight, diet, skin color and socio-economic status did not influence vitamin D levels. Conclusions: This is the first study of vitamin D status among the school-age children of Kerala. This paper adds further evidence to the reports indicating high prevalence of subclinical VDD among children across India and calls for action.